The Impact of Individual Needs on Employee Performance while Teleworking - Sonali Bhattacharya; Priyanka Mittal (Australasian Accounting, Business and Finance Journal, 2020)
Due to change in work structures, the boundaries of private life and office work are getting depleted. There are various factors that may impact the performance of an employee, and they need to be identified. As different people in a company may have different home environments (family size, marital status, electricity, Wi-Fi, dedicated laptop with required software to teleconnect, noise and other distractions based on location of home, etc.), the telework setting varies and conflicts may arise during work and home transitions, especially when the dominant needs of a person are not met. Acquired Needs Theory by David McClelland classifies our needs into Achievement, Affiliation and Power and this paper aims to study the conflicts (Home-to-Work conflict or HTWC and Work-to-Home conflict or WTHC) that may arise within individuals due to the variation in their dominant needs. Employees presently working from home were administered a questionnaire that comprised items to measure the dominant needs of individuals. The questionnaire also had items to gauge what kind of issues/conflicts employees face while teleworking, and their coping behaviour. Responses were collected on a 7-point Likert Scale. Control variables like the level of restrictions in going out due to pandemic were also considered. The study established that among all the control variables, the number of hours spent working and family type has significant impact on both the conflicts, WTHC and HTWC. Also, people with different dominant needs have different impacts on conflict outcomes. Changing work landscape requires an organisation’s responsiveness to understand the interaction of individual personalities with their work and how future telework can be made more effective. People with a high Achievement need may face more WTHCs and those with a high Affiliation need may face more HTWCs. As the Power need increases, the person may face fewer WTHC and HTWC. These insights can be used by the organisation to drive the need among individuals so that they remain inclusive and satisfied.
Keywords: Acquired Needs Theory; telework; conflicts; needs; Achievement; Power; Affiliation; WTHC; HTWC